2015
DOI: 10.1146/annurev-conmatphys-031214-014614
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Stability in Structural, Spin, and Electron Glasses

Abstract: We revisit the concept of marginal stability in glasses, and determine its range of applicability in the context of avalanche-type response to slow external driving. We argue that there is an intimate connection between a pseudo-gap in the distribution of local fields and crackling in systems with long-range interactions. We show how the principle of marginal stability offers a unifying perspective on the phenomenology of systems as diverse as spin and electron glasses, hard spheres, pinned elastic interfaces … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
264
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(278 citation statements)
references
References 123 publications
13
264
1
Order By: Relevance
“…20 it was observed that contact-opening excitations in packings are marginally stable, so that the bounds 14 and 15 are satisfied with equality, with numerical values γ ≈ 0:4, θ ℓ ≈ 0:17, and θ e ≈ 0:44. Saturation of [15] was recently proven for certain dynamics (38). Assuming such marginal stability, it follows that θ f = θ ℓ < θ e and the exponent θ e can be determined from θ e = 2θ f =ð1 − θ f Þ ≈ 0:41, a value consistent with the direct measurement 0.44.…”
Section: Hard Spheressupporting
confidence: 66%
“…20 it was observed that contact-opening excitations in packings are marginally stable, so that the bounds 14 and 15 are satisfied with equality, with numerical values γ ≈ 0:4, θ ℓ ≈ 0:17, and θ e ≈ 0:44. Saturation of [15] was recently proven for certain dynamics (38). Assuming such marginal stability, it follows that θ f = θ ℓ < θ e and the exponent θ e can be determined from θ e = 2θ f =ð1 − θ f Þ ≈ 0:41, a value consistent with the direct measurement 0.44.…”
Section: Hard Spheressupporting
confidence: 66%
“…Moreover, it is certainly worth exploring the implications of our results on the statistics of avalanches induced by strain, generalizing the ideas originally put forward in ref. 2, and connect our results with studies on shear-transformation-zone interactions 21 . All these factors open the way towards new research directions aimed at revealing the true nature of glasses.…”
supporting
confidence: 67%
“…In ref. 21, it was argued that this is due to the way in which they are formed: unstable elementary excitations progressively rarify during a crunch, and jamming takes place exactly when no excitation is left, leaving the system solid but at the verge of instability (that is, marginally stable). Within mean-field theory, the results found at jamming are a consequence of a more general marginal stability: the appearance of multiple competing particle arrangements is accompanied by the emergence of long-range power-law correlations and soft modes.…”
mentioning
confidence: 99%
“…It has been suggested by previous work [28,31,32] that, below the threshold T * , the system might be "marginally stable", i.e. characterized by a diverging correlation length of particle displacements, and a diverging χ AB , also associated to delocalized soft vibrational modes [40,41]. However, Ref.…”
Section: Aging and Heterogeneity Of Individual Samplesmentioning
confidence: 99%